Synergetic Effect of Potassium Iodide and Miana (Coleus scutellaroides (L.) Benth.) Leaves Extract on Mild Steel in HCl Medium - Putri, Sanaq Elfira; Gusniardi, Vira Anggita; Suryati, Suryati; Emriadi, Emriadi (Hydrogen: Jurnal Kependidikan Kimia, 2023)
Due to its low carbon content, mild steel is prone to corrosion. Therefore, corrosion inhibitors are needed to decrease the corrosive rate of mild steel. This research aims to investigate the influence of adding potassium iodide to miana leaves extract (Coleus scutellaroides (L.) Benth.) (MLE) on the corrosion rate of mild steel, identify the type of adsorption, synergistic effects and characterize the surface of mild steel both before and after the addition of potassium iodide. The weight loss method is employed to test the corrosion rate, and the type of adsorption is identified through thermodynamic calculations. Surface characterization is evaluated using Fourier Transform Infrared (FTIR) and Scanning Electron Microscopy (SEM). As potassium iodide is added, the weight loss findings show an increase in inhibitory efficiency. When potassium iodide concentration was 0.4 g/L and temperature was 30Â°C, the maximum inhibitory efficiency was attained, which was 92.784%. Characterization analysis indicates the interaction between potassium iodide and MLE with the surface of mild steel. This research has not been explored yet and is expected to provide information on the use of potassium iodide and MLE as environmentally friendly corrosion inhibitors.